2022
DOI: 10.1001/jamaoncol.2022.5041
|View full text |Cite
|
Sign up to set email alerts
|

Association of Immune-Related Adverse Event Management With Survival in Patients With Advanced Melanoma

Abstract: ImportanceManagement of checkpoint inhibitor–induced immune-related adverse events (irAEs) is primarily based on expert opinion. Recent studies have suggested detrimental effects of anti–tumor necrosis factor on checkpoint-inhibitor efficacy.ObjectiveTo determine the association of toxic effect management with progression-free survival (PFS), overall survival (OS), and melanoma-specific survival (MSS) in patients with advanced melanoma treated with first-line ipilimumab-nivolumab combination therapy.Design, Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 32 publications
3
40
0
1
Order By: Relevance
“…This is, for instance, illustrated by the more acute onset, the possibility of complete irAE reversibility with adequate therapy and shorter time-to-response of biologicals [5]. Together with the concern that targeted immunosuppression may thwart antitumor immunity [6, 7], these observations underscore that evidence-based irAE treatment requires more profound biological understanding of specific mechanisms underlying ICI-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This is, for instance, illustrated by the more acute onset, the possibility of complete irAE reversibility with adequate therapy and shorter time-to-response of biologicals [5]. Together with the concern that targeted immunosuppression may thwart antitumor immunity [6, 7], these observations underscore that evidence-based irAE treatment requires more profound biological understanding of specific mechanisms underlying ICI-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, whilst the need for irAE treatment with immunosuppression within two months of CPI initiation has been suggested to be deleterious for cancer outcome ( 92 ), the confounding impact of premature CPI cessation in this context also remains unclear. The same important caveat applies to data suggesting escalation of immunosuppression, to include targeted interventions including biologic drugs on top of glucocorticoids ( 93 ). It should also be remembered that high-dose glucocorticoid use is itself associated with considerable morbidity ( 94 96 ).…”
Section: Conclusion and Therapeutic Considerationsmentioning
confidence: 99%
“…In Reply We would like to thank Reid et al for their valuable comments on our cohort study in which we demonstrated an association between dual immune checkpoint inhibitors (ICIs) and impaired survival in patients with grade 3 or higher immune-related adverse events (irAEs) who received second-line immunosuppressants compared with those who only received corticosteroids . Reid and colleagues raise important questions concerning possible biases in our analyses with respect to steroid use and the potential for immortal time bias.…”
mentioning
confidence: 94%